KEPEMILIKAN PEMERINTAH, KEPEMILIKAN ASING, DAN KREDIT VALUTA ASING BANK DI INDONESIA - Setiawan, Rahmat; Putri, Octavia Reniar (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2019)
High foreign participation in the emerging banking markets is because of many foreign customers who opened their businesses in the host country, and therefore they need ï€nancing from familiar banks. This study aims to understand the effect of state ownership and foreign ownership on bank loans in foreign currency. We use 116 samples of conventional commercial banks in Indonesia during 2010-2017, with 832 observations. The results of multiple regression show that banks with state ownership have lower foreign currency loans than non-state ownership and banks with foreign ownership have higher foreign currency loans than domestic ownership. These results indicate that eventhough the presence of foreigners will increase loans in banking industry, but these loans are in foreign currency, which indirectly shows that their contribution will be used more by foreigners themselves.